2011
DOI: 10.1177/1545109710397893
|View full text |Cite
|
Sign up to set email alerts
|

HIV Postexposure Prophylaxis (PEP) in a Nigerian Tertiary Health Institution

Abstract: A total of 116 clients sought for PEP services during the study period. The commonest setting of exposure was needle injury (44.8%). Half of the clients presented within 24 hours following exposure. Being a male and knowing HIV status of source patient independently increased the likelihood of early presentation following exposure (P < .05). None of the patients that obtained the PEP drugs came for follow-up visits. Conclusion/Recommendation: Late presentation for PEP services following exposure means that mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(39 citation statements)
references
References 7 publications
1
38
0
Order By: Relevance
“…The study revealed that more females enrolled into the PEP programme than males, with the majority being in the youth age bracket. This result was similar to the findings of another study (Onyedum et al, 2011). Since most of the cases with reported nature of exposure were due to occupational exposure, the young age may be due to the naivety of healthcare workers beginning their practices.…”
Section: Demographic Characteristics Of Pep Enrolleessupporting
confidence: 90%
See 1 more Smart Citation
“…The study revealed that more females enrolled into the PEP programme than males, with the majority being in the youth age bracket. This result was similar to the findings of another study (Onyedum et al, 2011). Since most of the cases with reported nature of exposure were due to occupational exposure, the young age may be due to the naivety of healthcare workers beginning their practices.…”
Section: Demographic Characteristics Of Pep Enrolleessupporting
confidence: 90%
“…There was no evidence to show that the other enrollees reported to the clinic for the follow-up such that the nonconduction of the tests cannot be solely blamed on the clinic. A study conducted in the same clinic vindicates the position as it showed that none of the enrollees returned to the clinic for follow-up counseling and test (Onyedum et al, 2011). This behaviour is however in contradiction to the result of a study in San Francisco in which 75% of those enrolled returned for HIV antibody test at the sixth month follow-up (Khan et al, 2001).…”
Section: Compliance Of Apin-cdc Clinic Unth Enugu Pep Practice Withmentioning
confidence: 91%
“…The majority (207 out of 281) of HCWs in our study were doctors and students. Doctors and students are often involved in invasive medical procedures, which places them at risk of being exposed to infectious material [ 7 , 9 , 11 , 25 ]. Furthermore, students and doctors with less than a year’s experience, are prone to occupational exposure because of their inexperience [ 7 , 9 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the level of awareness and knowledge demonstrated by the family physicians in our study, majority of those that had been exposed to NSI did not access HIV PEP, even though most of their institutions had existing HIV PEP policies and protocols. This knowledge–practice gap provides opportunities for targeted interventions to improve HCWs access to existing policies and protocols for effective utilization of HIV PEP which is needed to prevent seroconversions from NSI and other modes of occupational exposure, especially since recent reports from Nigeria indicate that this knowledge–practice gap is generalized among those at risk 92021. Special programs to improve knowledge and increase access to HIV PEP targeting senior doctors should also be encouraged and instituted.…”
Section: Discussionmentioning
confidence: 99%